Farmco: The Complexity of Evaluating Suppliers. Issue 1 (1st November 2018) - Gerschberger, Markus; Manuj, Ila
Abstract : This case focuses on supplier management through quantitative and qualitative analysis of data from a real company. In the process of solving the case, students determine and operationalize what constitutes a critical supplier, analyse the data provided, and identify the most critical suppliers.